1988
DOI: 10.1185/03007998809111119
|View full text |Cite
|
Sign up to set email alerts
|

An open comparative study of two diuretic combinations, frusemide/amiloride (‘Frumil’) and bumetanide/potassium chloride (‘Burinex’ K), in the treatment of congestive cardiac failure in hospital out-patients

Abstract: Forty elderly patients, aged 68 to 89 years, with congestive cardiac failure, who were attending a hospital out-patients department, entered an open, parallel group, comparative study of two diuretic combinations, 40 mg frusemide plus 5 mg amiloride per tablet and 0.5 mg bumetanide plus 573 mg slow-release potassium chloride per tablet. Patients were assigned at random to receive one or other combination for 8 weeks, dosage being determined by the severity of the individual patient's condition (range 1 to 3 ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…One final assessment of the pharmacologic effects of torsemide on the myocardial tissue of patients with HF was conducted in 2 studies by L6pezet al 23 ,24 Theseinvestigators tested the theorythat myocardial accumulation of collagen fibers leads to deterioration of left-ventricular function. This fibrosis is the result of increased synthesis by collagen fibroblasts and/ordecreased collagen degradation as a result of increased aldosterone," In the firststudy, changes in myocardial volume occupied by collagen, serum carboxy-terminal telopeptide of collagen type I, car': boxy-terminal peptideof procollagen type I (PIP),and indexes of collagen type I synthesisand degradation in patientsreceiving either furosemide or torsemide were compared.This was a randomized, open-label,parallel-group study of 36 While it is important to note the pharmacologic variations betweenthe loop diuretics, it is arguably more important to assess whether any of these differences translate into positiveclinicaloutcomes (Table 3). [25][26][27][28][29][30][31][32][33][34][35][36] Comparative Safety and Efficacy in Heart Failure: Furosemide vs Torsemide Murray et al 25 assessed the impact of furosemide and torsemideon hospitalreadmissions secondaryto HF exacerbations over a 12-month period.…”
Section: Pharmacologic Effects Of Torsemide In Patients With Heart Famentioning
confidence: 99%
“…One final assessment of the pharmacologic effects of torsemide on the myocardial tissue of patients with HF was conducted in 2 studies by L6pezet al 23 ,24 Theseinvestigators tested the theorythat myocardial accumulation of collagen fibers leads to deterioration of left-ventricular function. This fibrosis is the result of increased synthesis by collagen fibroblasts and/ordecreased collagen degradation as a result of increased aldosterone," In the firststudy, changes in myocardial volume occupied by collagen, serum carboxy-terminal telopeptide of collagen type I, car': boxy-terminal peptideof procollagen type I (PIP),and indexes of collagen type I synthesisand degradation in patientsreceiving either furosemide or torsemide were compared.This was a randomized, open-label,parallel-group study of 36 While it is important to note the pharmacologic variations betweenthe loop diuretics, it is arguably more important to assess whether any of these differences translate into positiveclinicaloutcomes (Table 3). [25][26][27][28][29][30][31][32][33][34][35][36] Comparative Safety and Efficacy in Heart Failure: Furosemide vs Torsemide Murray et al 25 assessed the impact of furosemide and torsemideon hospitalreadmissions secondaryto HF exacerbations over a 12-month period.…”
Section: Pharmacologic Effects Of Torsemide In Patients With Heart Famentioning
confidence: 99%
“…There have been a few head-to-head comparisons of loop diuretics in patients with HF. Small, open-label RCTs with short-term follow-up found few differences in symptoms or diuresis between furosemide and bumetanide [59][60][61]. However, others suggested that mortality, hospitalisation, symptoms, and quality of life were better with torsemide compared to furosemide [62][63][64]; a definitive trial followed (Table 3).…”
Section: Which Loop Diuretic To Use?mentioning
confidence: 99%
“…Preliminary studies suggest that bumetanide-induced hypokalaemia is less marked than that caused by frusemide. 25,26 However, it is possible that both the potassium-sparing effect of quinapril as an ACEI and the potassium supplement contained in the specific diet recommended for dogs with heart con-ditions 22 may have influenced these preliminary results. Urinary potassium FE rose considerably postadministration, a finding also reported by many authors.…”
Section: Clinicalmentioning
confidence: 99%